Optimal reproductive phenology under size‐dependent cannibalism. Issue 10 (16th April 2020) - Takashina, Nao; Fiksen, Øyvind
Abstract: Intra‐cohort cannibalism is an example of a size‐mediated priority effect. If early life stages cannibalize slightly smaller individuals, then parents face a trade‐off between breeding at the best time for larval growth or development and predation risk from offspring born earlier. This game‐theoretic situation among parents may drive adaptive reproductive phenology toward earlier breeding. However, it is not straightforward to quantify how cannibalism affects seasonal egg fitness or to distinguish emergent breeding phenology from alternative adaptive drivers. Here, we devise an age‐structured game‐theoretic mathematical model to find evolutionary stable breeding phenologies. We predict how size‐dependent cannibalism acting on eggs, larvae, or both changes emergent breeding phenology and find that breeding under inter‐cohort cannibalism occurs earlier than the optimal match to environmental conditions. We show that emergent breeding phenology patterns at the level of the population are sensitive to the ontogeny of cannibalism, that is, which life stage is subject to cannibalism. This suggests that the nature of cannibalism among early life stages is a potential driver of the diversity of reproductive phenologies seen across taxa and may be a contributing factor in situations where breeding occurs earlier than expected from environmental conditions. Abstract : Cannibalism introduces a trade‐off between breeding at the optimal time in the season and increased predation risk from offspring born earlier. We predict how size‐dependent cannibalism on eggs, larvae, or both changes emergent breeding phenology and find breeding that occurs earlier than the optimal match to environmental conditions. We show that emergent breeding phenology patterns at the level of the population are sensitive to the ontogeny of cannibalism.